Therapeutic Effects of Forest Bathing on Human Health: A Systematic Review - Samoraj, Adrianna; Zajączkowski, Jakub; Krzeszowska, Paulina; Stępniak, Kacper; Marrodán-Wojtczak, Karolina; Wilk, Jan; Jarmołowicz, Jakub; Kujawa, Aleksandra; Krochmal, Karolina; Kuźma, Radosław (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: This comprehensive review aims to synthesize and analyze the existing scientific literature concerning the multifaceted impact of forest bathing, also known as shinrin-yoku, on human health and overall well-being. We will delve into the historical origins of shinrin-yoku while also meticulously examining the specific health domains. Materials and Methods: A systematic search of the PubMed database was conducted to extract relevant articles published between 1975 and 2023. The search strategy employed the following key terms: "forest bathing," "shinrin-yoku," "human health," and "well-being." Results: The analysis of the retrieved data revealed a consistent pattern of beneficial physiological effects associated with forest bathing. Specifically, a reduction in heart rate, as well as systolic and diastolic blood pressure, was observed in individuals who participated in forest excursions. The biogenic volatile organic compounds (BVOCs) emitted by forest vegetation were shown to exert potent anti-inflammatory effects, inhibiting inflammatory processes implicated in conditions such as asthma, atopic dermatitis (AD), and rheumatoid arthritis (RA). Notably, a lower incidence of COVID-19 was observed in densely forested areas, potentially attributable to the natural barrier effect of forest vegetation against viral transmission and the lower levels of air pollution prevalent in these environments. Shinrin-yoku was also found to play a crucial role in maintaining mental health. In patients with dementia symptoms, forest bathing interventions resulted in improvements in language function and memory, among other cognitive domains. Conclusions: Forest bathing represents an accessible and cost-effective intervention that holds significant potential for enhancing human quality of life. Therefore, it should be considered as an integral component of a healthy lifestyle and incorporated into routine daily activities.